Educational manual for the care of patients in the post-operative period of myocardial revascularization: a tool for patients and families - Luana Llagostera Sillano Gentil; Rodrigo Marques da Silva; Sonia Betzabeth Ticona Benavente; Ana Lucia Siqueira Costa (Universidade Federal de Goias, 2017)
An educational manual for the self-care of revascularized patients after hospital discharge was created. It is a methodological study whose data collection occurred between February and April, 2012, with eight cardiology experts and 35 patients/families. Content and face validation were conducted with eight patients/families and eight experts. Of the proposed 46 items, patients/families rated 26 items (57%) as very important (agreement between 91.4% and 100%) and experts rated 29 items (63%) as very important (agreement equal to or over 75%). Thirty-six items, distributed in 26 categories, were selected for the final manual. There was 100% agreement between patients/families regarding content, language, and illustrations. The tool presented semantic validity and content adequacy for the population, because it was able to reduce complications resulting from lack of training for self-care, thus reducing the number of readmissions and hospital costs, in addition to systematizing post-operative teaching.